Merajut Benang Kusut Tragedi Kemanusiaan: Solusi Tasawuf bagi Krisis Kemanusiaan Kontemporer - Badarus Syamsi (Refleksi: Jurnal Kajian Agama dan Filsafat, 2009)
This article explores the solutions that ever presented by Islam especially through the mystical dimension in order to redirect people to realize the essence and recognize their God. This paper will answer the question of how to reconcile the concept of mysticism about human identity in a unified and how to reformulate the concept of Sufism of human that it shows more futuristic? To discuss these two issues, this paper will present some of the thought of Ibn Miskawayh, al-Ghazali, Ibn Arabi, Jalaluddin Rumi, and Said Nursi.